Inovasi Sistem Administrasi Sekolah Berbasis Web di Lingkungan Pondok Pesantren Al Madinatul Islamiyah Rumeneng Desa Paok Motong - Muhammad Atha’ Iqbal; Ratna Yuniarti (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to see the application of web-based administrative system innovation in maximizing administrative services. Using a qualitative approach, data was collected through interviews and literature study methods. The results of the study indicate that web-based administrative system innovation results in effective and efficient resource management, good data processing and information access, and transparency in administrative management. The findings outlined in this article have an important impact on the development and improvement of education in Islamic boarding schools.